Dietary Practices And Perceptions During Pregnancy And Lactation Among Women In Rural Sindhudurg: A Qualitative Study - Deshpande, Sonal; Potdar, Pallavi (Medical Technology and Public Health Journal, 2024)
Various regions of Maharashtra have different cultural practices. Pregnancy, childbirth, and lactation are circumstances where cultural beliefs strongly affect women’s dietary practices. A qualitative study was conducted to describe dietary practices and perceptions during pregnancy and lactation among women in rural Sindhudurg. A cross-sectional study was conducted among pregnant and lactating women, women involved in cooking for their families, and frontline workers at the rural field practice area of SSPM Medical College, Sindhudurg. A homogenous group for Focused group discussions and a typical case method for In-depth Interviews were used. The mean age of the total 66 participants was 49.2 + 12.3 years. All the pregnant women agreed that their diet should include fruits, sprouts, and milk. There was a special diet for lactating women, especially during puerperium. Methi laddu, dink ladoo, and dry fruits laddu were consumed by lactating women as galactagogues. They had various myths regarding foods to be avoided during pregnancy. Lactating mothers believed that their diet does affect breast milk composition. There were myths regarding foods that, when consumed by lactating women, may lead to specific symptoms or conditions in babies. The Mean dietary diversity scores of pregnant and lactating mothers were low and were lowest during puerperium. Though many pregnant women know nutritious food, affordability and time availability are constraints. Dietary restrictions, especially during the early postpartum period, led to less dietary diversity. Some of the beliefs are deep-rooted and need to be more easily amenable. Keywords: Diet, lactation, pregnancy, qualitative, rural Sindhudurg